(untitled) (Revista Venezolana de Salud Pública, 2018)
With its slogan "To health for a health conscience", the magazine ser was presented as a fortnightly publication of the Division of Health Education of the Ministry of Health and Social Assistance of Venezuela, its distribution was free and its content could be reproduced freely without prior consultation, provided that they were not pursuing lucrative purposes or commercial propaganda. It was published monthly (two numbers came out together a month) and had a print run of 60,000 copies in full color. Its headquarters was in Caracas, Venezuela, on Avenida José Antonio Páez, Saumell Palace Building, El Paraíso. The Journal was mainly addressed in a pleasant, simple and didactic way different topics of Public Health, Parasitology, Microbiology, Childcare, Nutrition, Mental Health, Road Health, Dentistry, Prevention against Drugs, School Health, Nursing and less frequently other topics as Botany and Entomology.